2017
DOI: 10.1177/1753193417729579
|View full text |Cite
|
Sign up to set email alerts
|

The Polish version of the Michigan Hand Outcomes Questionnaire: Cross-cultural adaptation, reliability, construct validity, and measurement error

Abstract: The aims of this study were to translate the Michigan Hand Outcomes Questionnaire into the Polish language and to test the measurement properties of its quality criteria. A total of 120 patients with hand complaints completed the Polish Michigan Hand Outcomes Questionnaire and the Disabilities of the Arm, Shoulder, and Hand questionnaire on the first assessment, along with the grip test, pinch test, and pain sore assessed using a visual analogue scale during activity. After 7 days, 76 patients completed the Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
4
5
1
Order By: Relevance
“…It tells that the items in the same subscale are correlated with each other and measuring the same construct. Our results on internal consistency of the MHQ subscales are similar to those in other language versions of the MHQ (10)(11)(12)(13)(14). There were no floor or ceiling values except for the esthetics subscale.…”
Section: Discussionsupporting
confidence: 85%
“…It tells that the items in the same subscale are correlated with each other and measuring the same construct. Our results on internal consistency of the MHQ subscales are similar to those in other language versions of the MHQ (10)(11)(12)(13)(14). There were no floor or ceiling values except for the esthetics subscale.…”
Section: Discussionsupporting
confidence: 85%
“…The ICC of the total score of the MHQ-Thai version showed excellent test-retest reliability for patients with hand injuries. The ICC for each domain was also good to excellent, which was a similar result to the original MHQ and the other translated MHQs [5, 16, 18, 19, 21, 22]. This indicated that the domains in the MHQ-Thai version were highly reliable in repeated testing and were stable over time.…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, aesthetics had a low-to-moderate correlation with hand function, even though it was an important outcome for patients with a hand injury. The construct validity of the MHQ-Thai version was in line with the original MHQ and other translations [5, 16].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, this tool has been proven to be valid and has demonstrated a high standardized response mean (SRM) in many types of hand/wrist injuries and disorders [10,14,[18][19][20][21][22]. The MHQ has been translated and cross-culturally adapted into many languages including Turkish [23], Brazilian [24], Korean [25], Japanese [26], German [27], Persian [28], Polish [29], French [30], Finnish [31] and Thai [32].…”
Section: Introductionmentioning
confidence: 99%